Planning of LTE-Apro Network using Licensed Assisted Access combining Spectrum Licensed 1800MHz and Unlicensed 5GHz - Mubarok, Arif; Usman, Uke Kurniawan; Fitrianto, Galih Purnomo (International Journal of Advanced Science Computing and Engineering, 2019)
The number of activities in the room results in an increase inthe amount of traffic which means a large surge in cellular users. Aslarge data traffic increases, limited spectrum is available and highspectrum costs, wireless service providers respond by makingadjustments to LTE technology. With the presence of LTE-APsupported by an unlicensed spectrum, Telkomsel operators can enjoythe unlicensed spectrum to increase capacity and throughput.Cellular network planning uses 2 scenarios to get the best solution,Scenario 1 is planning the LTE Network with a bandwidth of 20 MHz inband 3 and using a 4x4 MIMO antenna. , scenario 2 planning the LTEAdvancedPro network uses the LAA method by combining theunlicensed 20 MHz spectrum in band 36 and a licensed 20 MHzsprectrum in band 3 and using a 2x2 MIMO antenna. analysis andsimulation using U-Net V500 software.The results of the LTE network planning simulation obtained theaverage value of RSRP 77 -77.71 dBm, SINR ≥  11.88 dB, Throughput≥  37.079 Mbps and User connected = 98.00%, while the LTE-APaverage value of RSRP ≥  -73.51 dBm, SINR ≥  17.02 dB , Throughput ≥ 49,739 Mbps and User connected = 100.00%. Based on the simulationresults, the LTE-AP network planning is very good to be implementedin the city of Bandung, the best solution choice to overcome thelimitations of Telkomsel spectrum with the network performance that isvery good in terms of coverage and capacity.